2004
DOI: 10.1074/jbc.m312763200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Splicing Variants of Rapostlin, a Novel Rnd2 Effector that Interacts with Neural Wiskott-Aldrich Syndrome Protein and Induces Neurite Branching

Abstract: Rho family GTPases regulate neuronal morphology.Rnd subfamily is a new branch of Rho family GTPases. Of these GTPases, Rnd2 is specifically expressed in brain. We recently identified Rapostlin as a novel effector of Rnd2. Rapostlin induces neurite branching in response to Rnd2 in PC12 cells. During the cloning of Rapostlin, we have found two mainly expressed splicing variants of Rapostlin (renamed as RapostlinL), RapostlinM and RapostlinS, lacking 29 residues and 61 residues within the unique insert region at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…Immunoblotting-Immunoblotting was performed as described previously (11). Briefly, proteins were separated by SDS-10% PAGE and were electrophoretically transferred onto a polyvinylidene difluoride membrane (Millipore Corporation, Bedford, MA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunoblotting-Immunoblotting was performed as described previously (11). Briefly, proteins were separated by SDS-10% PAGE and were electrophoretically transferred onto a polyvinylidene difluoride membrane (Millipore Corporation, Bedford, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid Constructions and Antibodies-Rat Toca-1 was cloned as described previously (11) using RT-PCR with rat brain RNA as a template. cDNAs encoding the full-length Toca-1L (amino acids 2-609), Toca-1S (amino acids 2-551), Toca-1L-K576 (amino acids 2-609), Toca-1L-IST (amino acids 2-609), Toca-1L-⌬C (amino acids 2-371), Toca-1L-⌬N (amino acids 389 -609), and Toca-1L-QQ (amino acids 2-609) were subcloned into expression vector pCMV (Clontech, Mountain View, CA) encoding an initiating Met followed by the Myc epitope tag or enhanced green fluorescent protein (EGFP) sequence at the N terminus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine direct interaction between the FRS2␤ and Rnd1, dot blot assay was performed as described previously (21). Five g of GST and GST-fused FRS2␤ (amino acids 247-493) were spotted onto a nitrocellulose membrane and allowed to dry for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, a previous study demonstrated that the interaction of Rnd2 with plexin D1 inhibits neurite outgrowth in cortical neurons (Uesugi et al, 2009). Finally, because Rnd2 modulates actin dynamics through interaction with the WASP proteins (Kakimoto et al, 2004), it is highly possible that increased Rnd2 levels might alter BSC neurite outgrowth, a process that is at the base of both glia-guided migration and CC formation.…”
Section: Coup-tfi Promotes Bsc Radial Migration and Callosal Axon Elomentioning
confidence: 99%